Efektivitas Pelatihan Tenis Meja Pada Siswa Kelas VII dan IX SMP Islam Muqorrobin Singosari - Junaidi, Ahmad; Artanty, Ary; Lufthansa, Luthfie; Khotimah, Khusnul; Amir Kullal, Moh.; Setiawan, Deny; Pratama, Risco Arief (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2024)
Learning effectiveness is the success of teachers and students in achieving learning goals. The existence of effective learning can improve learning outcomes. Physical Education, Sports and Health (PJOK) has an important role in the internalization of character-based education today. The independent curriculum which is currently the trigger demands that teachers must be able to facilitate students in the form of students' character, talents and interests. However, there are several factors that make the talent for playing table tennis among Class VII and IX students at Muqorrobin Islamic Middle School very low, including a lack of knowledge and training to play table tennis properly and correctly. This became the basis for the author to carry out table tennis training for 2 months with good results, namely the students were very happy with this training, those who initially didn't like table tennis became like it and their ability to play table tennis became even better.